Pendidikan Hukum Di Indonesia: Tinjauan Dalam Konteks Pendidikan Kewarganegaraan - Kurniyawan, Handi; Moeslim, Achmad Hafy Akmal (University of Muhammadiyah Malang, 2024)
The purpose of writing this article is to analyze the development of legal education in Indonesia over time from the perspective of Citizenship Education, especially within the school environment. The method used in this research is normative legal research, enriched with literature studies. This research is motivated by various incidents of legal violations committed by different parties, reported through both print and electronic media. In fact, the existing legal rules in society are meant to serve as guidelines and directions for individuals and the community in their behavior and interactions with others, thus creating security, peace, and prosperity. Therefore, it is essential that legal education is instilled and taught from an early age. One effective and systematic avenue for teaching and internalizing legal education in society is through Citizenship Education in schools. This is because the subject includes legal material, both explicitly and implicitly. The results of this study indicate that legal content is taught at every grade level/phase with the aim of strengthening students' character, particularly their public character, one of which is adhering to the prevailing legal rules. Moreover, teaching Citizenship Education as legal education to students also needs to be balanced with teachers setting a good example to ensure that the legal education is effective.